Interaksi Kapang Patogen Fusarium oxysporum dengan Bakteri Kitinolitik Rizosfer Tanaman Jahe dan Pisang - Ferniah, Rejeki Siti; Pujiyanto, Sri; Purwantisari, Susiana; Supriyadi, Supriyadi (Jurnal Natur Indonesia, 2011)
Fusarium oxysporum is a pathogenic fungi for many plants. The fungi have chitin cell wall that can be degraded by chitinase fromchitinolytic bacteria. Aim of this research is determine how the interaction between the bacteria and F.oxysporum. Bacteria were isolatedfrom plant rizosfere. Chitinolytic activity were measured based on the clear zone around the colony in chitin medium. Bacteria and fungiinteraction were determined by an antagonistic test. This research showed that there were 9 chitinolytic bacteria. J4 and P3 had highchitinolytic index, that are 3 and 3.33, respectively. The two isolates antagonist to F.oxysporum, which the bacteria prevent growth of thefungi. The J4 and P3 are alternative biofungicide for F.oxysporum.